Decentralised Nurseries for Promotion of Social forestry - Hegde, Narayan G. (Indian Forester, 2000)
Decentralised nursery management is the key to people's participation in Social Forestry. Depending on the facilities, the nurseries were c1assified as permanent, semi-permanent and temporary nurseries. However, with the involvement of the local people, the choices of species are shifting towards Non-Wood Forest Products apart from fruit and timber species. Establishment of nurseries to raise such species at the grassroots level can encourage the farmers to take up afforestation on their marginal and wastelands while creating opportunities for small farmers and women to generate sustainable livelihood. Quality of the plants further determine the success and profitability of such decentralised nurseries. Selection of suitable tree species and superior varieties, production of plants by vegetative methods, raising of healthy and hardy plants free from pests and diseases, use of suitable containers to transport the plants economically without damage, would contribute to the quality of the nurseries. Macro propagation technique can be useful to multiply most of the tree species at a lower cost than propagules from tissue culture. BAIF has already standardised the macro-propagation protocol for Neem, Bamboo, Casuarina, Shisham, Pongamia and Tamarind species. Use of gunny cloth to wrap the pot mixture with the root system has also been developed to facilitate easy transportation of plants.